Systematic Review of Sex and Gender Effects in Traumatic Brain Injury: Equity in Clinical and Functional Outcomes - Mollayeva, Tatyana; Mollayeva, Shirin; Pacheco, Nicole; Colantonio, Angela (Frontiers in Neurology, 2021)
Background: Although traumatic brain injury (TBI) is a leading cause of death and disability in male and female patients worldwide, little is known about the effect of sex and gender on TBI outcomes. Objectives: This systematic review summarises the evidence on the effect of sex and gender on core TBI outcomes. Methods: All English language studies from six literature databases that addressed core outcomes in adults with TBI and included sex or gender, TBI severity and age in their analyses were considered eligible. Two reviewers extracted data, and two reviewers assessed study quality using tools recommended by the National Institutes of Health. The results were sorted according to time post injury, injury severity, gender equity ranking of the study’s country of origin, and outcomes studied. The results from the included studies were grouped based on the approach taken in reporting their respective findings. Results and limitations: Of 172 articles assessed, 58 studies were selected, comprising 1,265,955 participants with TBI (67% male across all studies) of all injury severities. All studies were conducted in countries with a very high or high human development index, while the gender inequality index varied. While the heterogeneity across studies limited any meaningful conclusions with respect to the role of sex and gender, we did observe that as gender equality ranking improved, differences between male and female participants in outcomes would diminish. Inclusion of social equity parameters in the studies was limited. Conclusions and implications: The nonuniform findings observed bring forth the need to develop and use a comprehensive and consistent methodology in the study of sex and gender post-TBI, incorporating social equity parameters to uncover the potential social underpinnings of gender effects on health and functional outcomes. Registration number: CRD42018098697.